THE INFLUENCE OF COOPERATIVE LEARNING MODEL AND LEARNING MOTIVATION ON LEARNING OUTCOMES OF CLASS IV STUDENT PPKN AT SD NEGERI 050601 KUALA DISTRICT - Sri Eka Hariani; Deny Setiawan; Daulat Saragi (Sensei International Journal of Education and Linguistic, 2021)
This study aims to analyze: (1) the influence of the cooperative learning model is higher than the conventional learning model; (2) the learning outcomes of students who have high learning motivation are higher than students who have low learning motivation (3) the interaction between cooperative learning models and student learning motivation influences student learning outcomes. The research was in the form of a Quasi Experimental Design with a 2x2 factorial. The instruments used were the PPKn learning outcomes test and the Learning Motivation instrument. Data analysis used two-way ANOVA. The results showed: (1) There is an effect of the cooperative learning model on student PPKn learning outcomes in class IV SD Negeri 050601 Kuala District; (2) The learning outcomes of students who have high learning motivation are higher than students who have low learning motivation; (3) There is an interaction between the Cooperative learning model and learning motivation on the learning outcomes of Student PPKn at SD Negeri 050601 Kuala District.